1997
DOI: 10.1063/1.872229
|View full text |Cite
|
Sign up to set email alerts
|

On the Bernstein–Landau paradox

Abstract: The essence of the Bernstein–Landau paradox is that in a stable unmagnetized plasma electrostatic waves exhibit collisionless Landau damping, while in a magnetized plasma the Bernstein modes, perpendicular to the magnetic field, are exactly undamped, independent of the strength of the magnetic field. This problem is the subject of the present study. An analytical solution of the initial value problem for perturbations perpendicular to the magnetic field is given, which is a generalization of the well-known Lan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
17
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 12 publications
3
17
0
Order By: Relevance
“…This problem was investigated theoretically by Sukhorukov and Stubbe (1997) who derived analytical solutions of the problem. In Fig.…”
Section: Electron Bernstein and Upper Hybrid Waves In Magnetized Pmentioning
confidence: 99%
See 1 more Smart Citation
“…This problem was investigated theoretically by Sukhorukov and Stubbe (1997) who derived analytical solutions of the problem. In Fig.…”
Section: Electron Bernstein and Upper Hybrid Waves In Magnetized Pmentioning
confidence: 99%
“…In Fig. 12, we have compared a numerical solution of the Vlasov equation with the analytic solution of Sukhorukov and Stubbe (1997) for a wave with the wavenumber k x = 0.4 r −1 D and with different values on the magnetic field, such that ω ce /ω pe = 0.4/10, 0.4/7 and 0.4/4, where ω ce = eB ext /m e . The numerical result obtained from the Vlasov simulation can be seen in Fig.…”
Section: Electron Bernstein and Upper Hybrid Waves In Magnetized Pmentioning
confidence: 99%
“…11 shows the effect of an increasing magnetic field on the time oscillations. According to the Shukorukov and Stubbe theory, the effect of the Landau damping is visible in the first gyroperiod, but each cyclotron period the magnetic field raises the electric oscillations and recurrence peaks are strongly visible [23]. In correspondence to the strongest value of the magnetic field (B = 0.3), in Fig.…”
Section: A Test Case: the Bernstein-landau Paradoxmentioning
confidence: 95%
“…Another analytical and numerical study has been performed by Shukorukov and Stubbe [23], who solved numerically the dispersion relation of the Bernstein waves, and showed that, in the magnetized case, the effect of the Landau damping is visible in the first gyroperiod, for very brief time transients, but the waves are not damped at large times and the amplitude of the oscillations grows with increasing values of the external field. In this way, they solved the problem in linear approximation, paying attention to the time evolution of the density perturbation, under the effects of the magnetic field.…”
Section: A Test Case: the Bernstein-landau Paradoxmentioning
confidence: 98%
“…While linear collisionless damping vanishes when the wave propagates exactly perpendicular to the magnetic field [8,10], nonlinear collisionless damping persists due to surfatron acceleration [11] and stochastic heating [12]. To give a conservative estimation, note that the UH frequency is typically comparable to the gyrofrequency.…”
mentioning
confidence: 99%